Protocol for a scoping review study to identify and classify patient-centred quality indicators - Jolley, Rachel J (BMJ Open, 2017)
INTRODUCTION: The concept of patient-centred care (PCC) is changing the way healthcare is understood, accepted and delivered. The Institute of Medicine has defined PCC as 1 of its 6 aims to improve healthcare quality. However, in Canada, there are currently no nationwide standards in place for measuring and evaluating healthcare from a patient-centred approach. In this paper, we outline our scoping review protocol to systematically review published and unpublished literature specific to patient-centred quality indicators that have been implemented and evaluated across various care settings. METHODS AND ANALYSIS: Arksey and O'Malley's scoping review methodology framework will guide the conduct of this scoping review. We will search electronic databases (MEDLINE, EMBASE, the Cochrane Library, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Social Work Abstracts, Social Services Abstracts), grey literature sources and the reference lists of key studies to identify studies appropriate for inclusion. 2 reviewers will independently screen all abstracts and full-text studies for inclusion. We will include any study which focuses on quality indicators in the context of PCC. All bibliographic data, study characteristics and indicators will be collected and analysed using a tool developed through an iterative process by the research team. Indicators will be classified according to a predefined conceptual framework and categorised and described using qualitative content analysis. ETHICS AND DISSEMINATION: The scoping review will synthesise patient-centred quality indicators and their characteristics as described in the literature. This review will be the first step to formally identify what quality indicators have been used to evaluate PCC across the healthcare continuum, and will be used to inform a stakeholder consensus process exploring the development of a generic set of patient-centred quality indicators applicable to multiple care settings. The results will be disseminated through a peer-reviewed publication, conference presentations and a one-day stakeholder meeting.